2020
DOI: 10.1186/s12906-020-2848-2
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatography-mass spectrometry analysis, phytochemical screening and antiprotozoal effects of the methanolic Viola tricolor and acetonic Laurus nobilis extracts

Abstract: Background: The antiprotozoal and antioxidant activities of Viola tricolor and Laurus nobilis have been reported recently. Thus, the existing study pursued to assess the growth inhibition effect of methanolic extract of V. tricolor (MEVT) and acetonic extract of L. nobilis (AELN) against five Babesia parasites and Theileria equi in vitro and in vivo. Results: MEVT and AELN suppressed Babesia bovis, B. bigemina, B. divergens, B. caballi, and T. equi growth at halfmaximal inhibitory concentration (IC 50) values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…Olive leaf parts were washed using distilled water, then dried on an oven at 50 • C and ground to a fine powder using a blender [15,16]. We used 100% absolute ethanol as an organic solvent for extraction.…”
Section: Extraction Of Olive Leaf Extractsmentioning
confidence: 99%
“…Olive leaf parts were washed using distilled water, then dried on an oven at 50 • C and ground to a fine powder using a blender [15,16]. We used 100% absolute ethanol as an organic solvent for extraction.…”
Section: Extraction Of Olive Leaf Extractsmentioning
confidence: 99%
“…Medicinal plants have been a good source of new pharmacologically active molecules. For example, natural products could be a potential alternative for controlling the pathogen associated with diseases [1][2][3][4][5]. Recently, antibiotics and most drugs on the market have shown unwanted symptoms and the emergence of resistant pathogenic microorganisms, toxic effects related to these drugs, and withdrawal issues restricting their use in many countries [6], therefore, much attention has been paid to the herbal extracts and pharmacologically active molecules extracted from different plant species that are used previously in the traditional medicine [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Isoflavones (glabridin, 3 -hydroxy-4-O-methylglabridin, and hispaglabridin A) were also documented to possess potent antioxidant activity. Recently, isolated compounds, such as dehydro-stilbene derivatives have been documented as free radical scavengers [4,53]. Previous reports revealed that glycyrrhizin is broken down in the intestine and exhibits an anti-inflammation effect comparable with that of corticosteroid hormones, including hydrocortisone [54].…”
Section: In Vitro Pharmacological/biological Properties Of G Glabramentioning
confidence: 99%